A Case Report of Breast Fibromatosis Mimicking Breast Cancer - Dwirani Rosmala Pratiwi; Dyah Fauziah; Rizkie T Trisnawaty; Cindy Angelina Limantara (Indonesian Journal of Cancer, 2022)
Introduction: Breast Fibromatosis is a rare benign stromal tumor that accounts for 0.2% of all breast tumors. The clinical presentation and imaging features may mimic a malignant tumor. We reported a case of breast fibromatosis mimicking breast cancer.Case Presentation: A 22-years-old woman with a palpable breast lump was present and being examined. The ultrasound and mammography features suggested malignancy. Magnetic Resonance Imaging (MRI) and Multislice Computerized Tomography (MSCT) evaluation showed invasion of a tumor to muscle without intrathoracic involvement. A core biopsy was performed with the pathologic conclusion suspected as a phyllodes tumor with a differential diagnosis as mammary fibromatosis. The pathology result of intraoperative examination favor for fibromatosis. A wide excision procedure with a free margin could be achieved. The histopathological examination revealed spindle cells tumor infiltrating into muscle tissue. The result of immunohistochemistry examination excluded metaplastic carcinoma and Phyllodes tumor. Therefore, it confirmed a diagnosis of breast fibromatosis.Conclusions: Breast fibromatosis is a rare benign tumor of the breast that can mimic malignancy. This entity should be considered as one of the differential diagnoses in a patient with a breast lump. A pre-operative tissue diagnostic is mandatory to prevent radical treatment for this nonmalignant case.